2021
DOI: 10.3390/ani11020480
|View full text |Cite
|
Sign up to set email alerts
|

Do Camels (Camelus dromedarius) Need Shaded Areas? A Case Study of the Camel Market in Doha

Abstract: This study aimed at documenting whether dromedary camels have a preference for shade and how their behavior would change depending on the presence of shade and variable space allowance. A total of 421 animals kept in 76 pens (66 with shelter (Group 1), and 10 without shelter (Group 2)) at the camel market in Doha (Qatar) were recorded for 1 min around 11:00 a.m. when the temperature was above 40 °C. The number of animals in the sun and shade and their behaviors were analyzed using an ad libitum sampling method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Caretakers, furthermore, should avoid the formation of too numerous herds, paying attention to their composition in terms of age, sex, and relationships between members in order to limit competitive hierarchies and negative social interactions. The effect of space allowance on camels' welfare has been recently also evaluated by El Shoukary et al (2020) and Zappaterra et al (2021). Those authors showed that overcrowding had negative effects not only on behavior, increasing aggressions and stereotypies, but also on body conditions and reproductive performance of camels.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Caretakers, furthermore, should avoid the formation of too numerous herds, paying attention to their composition in terms of age, sex, and relationships between members in order to limit competitive hierarchies and negative social interactions. The effect of space allowance on camels' welfare has been recently also evaluated by El Shoukary et al (2020) and Zappaterra et al (2021). Those authors showed that overcrowding had negative effects not only on behavior, increasing aggressions and stereotypies, but also on body conditions and reproductive performance of camels.…”
Section: Discussionmentioning
confidence: 96%
“…These ndings may suggest that the presence of shade increased not only the thermal but also the social comfort of camels. It has recently been shown that camels have a preference for shade and express more behaviours indicating a quiet and positive state, such as recumbency and ruminating, in the shaded than sunny areas (Zappaterra et al, 2021). The opportunity to have positive experiences and express natural behaviours could have in uenced their intra-and interspecies relationships resulting in an improvement of welfare outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of each discriminant function was evaluated through its relative percentage of variance and Wilks’ lambda (the smaller Wilks’ lambda, the more important the function). The performances of the final DAs were, instead, estimated by running a leave-one-out cross-validation, which calculates the probability for each sample to be accurately classified in the correct organ [ 52 , 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, most of the research has been conducted in European countries for animals such as pigs, poultry, ewe, and dairy cattle (Main et al, 2007;EFSA, 2012b;Cook, 2017;Munoz et al, 2018;Tremolada et al, 2020). Among farm animals, the camel was rarely involved in studies related to welfare assessment (Pastrana et al, 2020;Zappaterra et al, 2021) and an ad hoc protocol for its welfare assessment has only recently been proposed (Padalino and Menchetti, 2021). This protocol includes a combination of animal-, resource-, and management-based measures assessed at three levels of investigation: using a face-to-face interview with the caretaker (caretaker level), checking the herd and the pen facilities (herd level), and inspecting individual camel behavior and health status (animal level).…”
Section: Introductionmentioning
confidence: 99%